Emotional, mental and physical health problems analysis system (EMPHASIS) / Lee Aik Ching - Lee, Aik Ching (2005)
Emotional, Mental and Physical Health Problems Analysis System (EMPHASIS) is my final year thesis title. This project documentations is an exercise submitted to Faculty Computer Science and Information Technology, U university of Malaya. EMPHASIS is design to evaluate the emotional, mental and physical health problems among the student of Faculty Science and Information Technology and recommend appropriate treatments for the students. EMPHASIS divided to six modules, there are survey from module, survey result module, generate report module, generate statistic module, student record module and treatment module. EMPHASIS is only display in English version. The Unified Process has been as the methodology to develop EMPHASIS. The technique such as questionnaire, discussion with supervisor and search from internet are used to gather important information. The major development tools that used to develop EMPHASIS are Windows XP Professional, Microsoft Visual Basic.Net, Microsoft SQL Server, ADO.NET, Macromedia Flash MX and Adobe Photoshop 7.0. As a conclusion, EMPHASIS is needed to be identify the level of emotional, mental and physical health problems and suggest suitable treatments to overcome these problems in order to help the students to excel academically.